Q 1: Divide (a^{4}4a^{3}2a^{2}9a4) by (a^{2}+2a+1). Quotient=(a^{2}6a+9) and Remainder=(21a13) Quotient=(a^{2}6a+9) and Remainder=(21a+13) Quotient=(a^{2}+6a+9) and Remainder=(21a13)

Q 2: Divide (9a^{4}6a^{3}+18a^{2}2a5) by (3a^{2}2a+2). Quotient=(3a^{2}4) and Remainder=(6a13) Quotient=(3a^{2}+4) and Remainder=(6a+13) Quotient=(3a^{2}+4) and Remainder=(6a13)

Q 3: Divide (a^{4}+a^{3}+6a^{2}+9a+7) by (a^{2}+a+2). Quotient=(a^{2}+4) and Remainder=(5a+1) Quotient=(a^{2}+4) and Remainder=(5a1) Quotient=(a^{2}+3) and Remainder=(5a1)

Q 4: Divide (6a^{4}+4a^{3}12a^{2}9a+6) by (3a^{2}+2a2). Quotient=(2a^{2}2) and Remainder=(2a^{2}5a+2) Quotient=(2a^{2}2) and Remainder=(2a^{2}5a2) Quotient=(2a^{2}+2) and Remainder=(2a^{2}5a+2)

Question 5: This question is available to subscribers only!

Question 6: This question is available to subscribers only!

